1993
DOI: 10.1016/s0022-5347(17)35911-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C Versus Estramustine in the Treatment of Hormone Resistant Metastatic Prostate Cancer: Thefinal Analysis of the European Organization Forresearch and Treatment of Cancer, Genitourinarygroup Prospective Randomized Phase III Study (30865)

Abstract: A total of 171 patients with progressive metastatic prostate cancer following hormonal therapy was randomized to receive either 560 to 700 mg. estramustine orally per day or 15 mg./m.2 mitomycin C by intravenous infusion every 6 weeks. The patients were recruited during a 2.5-year period, and 70% had undergone more than 1 previous therapy for prostate cancer, with some having received as many as 5 different previous treatments. The overall results were disappointing. The median time to progression was 5 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 3 publications
0
10
1
Order By: Relevance
“…As many as 43% of all patients were ≥70 years of age. A few years after initiation of trial 30893 two other reports described a relatively high level of toxicity in prostate cancer patients receiving MMC: Newling et al [21]reported nausea in 44% and vomiting in 32% of the patients with hormone–resistant prostate cancer receiving MMC, and in the report of Van Poppel et al [22], 17% of the patients had to discontinue treatment due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 43% of all patients were ≥70 years of age. A few years after initiation of trial 30893 two other reports described a relatively high level of toxicity in prostate cancer patients receiving MMC: Newling et al [21]reported nausea in 44% and vomiting in 32% of the patients with hormone–resistant prostate cancer receiving MMC, and in the report of Van Poppel et al [22], 17% of the patients had to discontinue treatment due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In six randomized NPCP trials, only 6 of 217 HRPC patients (2.8%) achieved an objective response to single-agent estramustine [10,[25][26][27][28][29]. No improvement in mean survival time was seen over patients who received no chemotherapy [10,25,30]. In addition, estramustine was not found to be superior to other single-agent regimens such as cisplatin, methotrexate, mitomycin C or vincristine.…”
Section: Estramustinementioning
confidence: 99%
“…There is also in vitro and in vivo evidence that estramustine binds to the nuclear matrix and possibly induces cell death via disturbances in macromolecular synthesis [22]. Estramustine has been extensively tested in HRPC patients, and as a single agent its benefits are minimal [10,[23][24][25][26][27][28][29][30][31][32]. The comparison of these studies, mainly from the pre-PSA era, is difficult due to the use of variable tumour response including the controversial category of stable disease as well as variable patient selection criteria [5].…”
Section: Estramustinementioning
confidence: 99%
“…Dependent on selection criteria of the patients and the definition of response criteria, EMP has shown variable response rates (Benson et al, 1986). In the clinical situation it has been difficult to prove the cytotoxic effect of single-drug EMP therapy (Newling et al, 1993;Fossa et al, 1990), whereas the British Joumal of Cancer (1997) 76(1), [93][94][95][96][97][98][99] results of recent trials combining EMP with etoposide and vinblastine are more promising (Hudes et al, 1992;Seidnian et al, 1992;Pienta et al, 1994). The concomitant use of EPR precludes any statement about EMP-induced bone marrow suppression in our trial.…”
Section: Toxicitymentioning
confidence: 99%
“…No consensus exists on the optimum medical treatment of this condition, which conventionally comprises progressive disease in spite of castration levels of serum testosterone. The median survival of symptomatic patients with hormone-resistant prostate cancer (HRPC) is 8-10 months (Foss'a et al, 1992a;Newling et al, 1993). Androgen independence most probably reflects the selection of hormoneresistant cell clones.…”
mentioning
confidence: 99%